2021
DOI: 10.1038/s41467-021-25633-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants and regulation of spontaneous activity in GABAA receptors

Abstract: GABAA receptors are vital for controlling neuronal excitability and can display significant levels of constitutive activity that contributes to tonic inhibition. However, the mechanisms underlying spontaneity are poorly understood. Here we demonstrate a strict requirement for β3 subunit incorporation into receptors for spontaneous gating, facilitated by α4, α6 and δ subunits. The crucial molecular determinant involves four amino acids (GKER) in the β3 subunit’s extracellular domain, which interacts with adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have reported that GABRA1 gene encodes γ-aminobutyric acid type A receptor α1 subunit (GABRA1) is one subtype of the neurotransmitter γ-aminobutyric acid (GABA) activating GABA A receptors that act as the components of the gamma-aminobutyric acid signaling pathway [ 54 , 55 ]. The heteropentameric receptors are formed from an array of subunits (α1–6, β1–3, γ1–3, δ, ε, π, θ and ρ1–3), producing receptors with diverse functional and pharmacological properties [ 56 58 ]. The GABA A receptors are vital for controlling neuronal excitability and can display significant levels of constitutive activity that contributes to tonic inhibition [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that GABRA1 gene encodes γ-aminobutyric acid type A receptor α1 subunit (GABRA1) is one subtype of the neurotransmitter γ-aminobutyric acid (GABA) activating GABA A receptors that act as the components of the gamma-aminobutyric acid signaling pathway [ 54 , 55 ]. The heteropentameric receptors are formed from an array of subunits (α1–6, β1–3, γ1–3, δ, ε, π, θ and ρ1–3), producing receptors with diverse functional and pharmacological properties [ 56 58 ]. The GABA A receptors are vital for controlling neuronal excitability and can display significant levels of constitutive activity that contributes to tonic inhibition [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heteropentameric receptors are formed from an array of subunits (α1–6, β1–3, γ1–3, δ, ε, π, θ and ρ1–3), producing receptors with diverse functional and pharmacological properties [ 56 58 ]. The GABA A receptors are vital for controlling neuronal excitability and can display significant levels of constitutive activity that contributes to tonic inhibition [ 58 ]. It has been established that the progesterone metabolite allopregnanolone, a potent modulator of the GABA A receptor, is sedative in high concentrations but may precipitate paradoxical adverse effects on mood at levels corresponding to luteal phase concentrations in susceptible women [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In each case, if the residue implicated is conserved across all three subunits the highlight is faded. Corresponding references for each position are indicated ( a–n ), where a: Torres and Weiss, 2002 ; b: Beckstead, 2002 ; c: Miller et al, 2008 ; d: Nayak et al, 2012 ; e: Purohit and Auerbach, 2009 ; f: Taylor et al, 1999 ; g: Sexton et al, 2021 ; h: Alves et al, 2011 ; i: Hannan and Smart, 2018 ; j: Pan et al, 1997 ; k: Mukhtasimova et al, 2009 ; l: Ohno et al, 1995 ; m: Grosman and Auerbach, 2000 ; n: Engel et al, 1996 .
Appendix 1—figure 2.
…”
Section: Multiple Sequence Alignmentsmentioning
confidence: 99%
“…Provided is the multiple sequence alignment ( Supplementary file 1 ) used to identify residues that differ between β Anc , β AncS , and the human β-subunit, and that also align with residues shown to be important for homomeric pLGIC assembly ( Alves et al, 2011 ; Hannan and Smart, 2018 ; Sexton et al, 2021 ; Taylor et al, 1999 ) and spontaneous activity ( Beckstead, 2002 ; Engel et al, 1996 ; Grosman and Auerbach, 2000 ; Miller et al, 2008 ; Mukhtasimova et al, 2009 ; Nayak et al, 2012 ; Ohno et al, 1995 ; Pan et al, 1997 ; Purohit and Auerbach, 2009 ; Torres and Weiss, 2002 ; Appendix 1—figure 1 ). Also shown is a local alignment of the second transmembrane region (M2) of the adult human muscle-type subunits (α-, β-, δ-, and ε-subunits), as well as β Anc and β AncS ( Appendix 1—figure 2 ) highlighting differences in well-characterized determinants of single-channel conductance ( Imoto et al, 1991 ; Imoto et al, 1988 ) and open-channel block ( Charnet et al, 1990 ; Leonard et al, 1988 ; Pascual and Karlin, 1998 ).…”
Section: Multiple Sequence Alignmentsmentioning
confidence: 99%
“…In both cultured neurons and hippocampal brain slices these events correlate with sustained increases in the efficacy of tonic inhibition ( Abramian et al, 2010 , 2014 ; Adams et al, 2015 ; Modgil et al, 2017 ). Phosphorylation of the β3 subunit can induce spontaneous channel openings of α4β3δ receptors which have an impact upon agonist/antagonist pharmacology and neuronal excitability ( Wlodarczyk et al, 2013 ; O’Neill and Sylantyev, 2018 ; Dalby et al, 2020 ; Sexton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%